2022
DOI: 10.7150/ijbs.71862
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in atherosclerosis: Convergence on macrophages

Abstract: As the primary cells of atherosclerotic plaques, macrophages play a central role in the occurrence and progression of atherosclerosis (AS). In recent years, macrophages have received extensive attention as therapeutic targets. Exosomes, as natural nanoparticles, have high biocompatibility and strong targeting ability and have been widely studied as imaging agents and drug carriers. Studies on the relationship between atherosclerotic macrophages and exosomes have been focused on for the past few years. Neverthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 151 publications
0
10
0
Order By: Relevance
“… 180 Macrophages are one of the cells responsible for atherosclerosis; they form foam cells by phagocytosing lipid droplets and accelerating the progression of atherosclerosis. 181 , 182 Basu et al 183 reported that macrophage-specific deletion of RPL13 increases the susceptibility of ApoE knockout mice to high-fat diet-induced atherosclerosis. The protective effect of RPL13 on atherosclerosis may be related to its translational silencing activity: the deletion of RPL13 promotes the translation of mRNAs for CCL22, CXCL13, and CCR3 in macrophages, causing increased expression of inflammatory cytokines.…”
Section: Ribosomes and Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
“… 180 Macrophages are one of the cells responsible for atherosclerosis; they form foam cells by phagocytosing lipid droplets and accelerating the progression of atherosclerosis. 181 , 182 Basu et al 183 reported that macrophage-specific deletion of RPL13 increases the susceptibility of ApoE knockout mice to high-fat diet-induced atherosclerosis. The protective effect of RPL13 on atherosclerosis may be related to its translational silencing activity: the deletion of RPL13 promotes the translation of mRNAs for CCL22, CXCL13, and CCR3 in macrophages, causing increased expression of inflammatory cytokines.…”
Section: Ribosomes and Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
“…After polarization, macrophages secrete not only cytokines but also exosomes with distinct functions. As natural nanoparticles, exosomes have shown high biocompatibility and specific targeting ability, thus being widely employed as imaging agents and drug carriers in recent years [ 73 ]. For example, M1 macrophage-derived exosomes were used as nanoparticle coatings to target drug-resistant and metastatic tumors [ 74 ].…”
Section: Phenotype and Function Of Macrophages Post-mimentioning
confidence: 99%
“…Atherosclerosis is a chronic and progressive vasculature disease involving inflammation and oxidative stress [59,60]. Endothelial injury and dysfunction result in atherosclerosis and precede lipid deposition, infiltration of immune cells, and accumulation of lipid-rich foam cells [2,61 ].…”
Section: Atherosclerosismentioning
confidence: 99%